Crime of terrorism and mechanisms to combat it - Elgizuli, Alaeldin Mohamed Musa (Journal of Economic, Administrative and Legal Sciences, 2019)
The study discusses the concept of the crimes of terrorism, its types, methods and risks. It also relied on the historical inductive method based on the available data and facts about the phenomenon of terrorism and its dangers, as well as the legal approach to study the most prominent conventions, treaties and international documents. The study concluded that the crimes of terrorism have negative effects on the society in terms of security, social and economic, including the spread of violence and violation of human rights and high rates of poverty and unemployment as a result of hindering development in society, It also concluded with a number of recommendations, including benefiting from the various media in spreading awareness among all members of the society to know the seriousness of terrorist crimes, knowing the methods of combating them and how to report them, and developing security research centers and institutes to keep abreast of developments and international developments, And the importance of developing advanced training programs to qualify all employees of the security services competent to learn methods of combating terrorism and the development of security surveillance systems and benefit from the development of technology and modern technology.